A view from outside: sovereign CDS volatility as an indicator of economic uncertainty - Böck, Maximilian; Feldkircher, Martin; Raunig, Burkhard (Macroeconomic Dynamics, 2024)
This paper proposes the volatility of sovereign credit default swaps (CDS) as a measurement of economic uncertainty. Sovereign CDS provide protection against losses from sovereign defaults and are traded for almost all countries by the world’s largest financial institutions. The premium for protection, the so-called CDS spread, depends on a country’s economic conditions and provides an outside view from global financial institutions. Our empirical results show that the volatility of sovereign CDS spreads contains information about economic uncertainty. For a broad panel of 16 countries, we find that sovereign CDS volatility shares directional information with popular news-based economic policy uncertainty (EPU) indices. Using Bayesian panel vector autoregressions, we find similar responses of output and unemployment to shocks in CDS volatility, equity volatility, and EPU. Our results further suggest that sovereign CDS volatility primarily reflects economic and financial uncertainty rather than political uncertaint
Keywords: Credit default swap; directional forecasts; economic policy uncertainty; financial market volatility